Artificial Reefs in Florida 101: Effects on Fishers (and Divers))—Part 3 of an Artificial Reef Series - Lisa Chong; Angela B. Collins; Holly Abeels; Anna Braswell; Ana Zangroniz; Andrew Ropicki; Scott Jackson; Edward V. Camp (EDIS)
Increasingly, coastal managers are placing artificial reefs in marine waters. These long-lasting habitat alterations have measurable effects on fish, fishers, divers, fisheries, and marine social ecological systems. Understanding how artificial reefs function is necessary to make good decisions about future artificial reefs. Scientific research on many aspects of artificial reefs is not always summarized and explained. In response to this need, we designed a 4-part series called Artificial Reefs 101. This publication, part 3 of the Artificial Reefs series, explains how artificial reefs affect fishers and divers. It will help the interested public understand more about the ecological effects of artificial reefs and provide detailed information to stakeholders including management agencies, local governments, artificial reef manufacturers, and Extension agents, to allow for better-informed decisions about building and managing artificial reefs.